2012
DOI: 10.1890/120062
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for mitigating nitrous oxide emissions from fertilized cropping systems

Abstract: Nitrous oxide (N2O) is often the largest single component of the greenhouse‐gas budget of individual cropping systems, as well as for the US agricultural sector as a whole. Here, we highlight the factors that make mitigating N2O emissions from fertilized agroecosystems such a difficult challenge, and discuss how these factors limit the effectiveness of existing practices and therefore require new technologies and fresh ideas. Modification of the rate, source, placement, and/or timing of nitrogen fertilizer app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 52 publications
3
166
0
2
Order By: Relevance
“…Needed especially are additional studies in climate zones other than north temperate, in rice and upland grain crops, and with different fertilizer formulations and application timings. Further knowledge of the factors and practices that affect N 2 O emissions from agricultural soils is crucial not only for developing effective mitigation strategies for this important GHG but also for developing a more robust means for balancing the global N 2 O budget (18,23,35).…”
Section: Discussionmentioning
confidence: 99%
“…Needed especially are additional studies in climate zones other than north temperate, in rice and upland grain crops, and with different fertilizer formulations and application timings. Further knowledge of the factors and practices that affect N 2 O emissions from agricultural soils is crucial not only for developing effective mitigation strategies for this important GHG but also for developing a more robust means for balancing the global N 2 O budget (18,23,35).…”
Section: Discussionmentioning
confidence: 99%
“…Cantarella (2007), Ghiberto et al (2009), andGhiberto et al (2011) observed very little NO 3 -leaching from N fertilizers in sugarcane using fertilizers labeled with 15 N. Although losses of N as N 2 O are environmentally important, they are a small fraction of fertilizer costs, and sugarcane growers may not be willing to pay the cost of NIs if no yield increases accompany this environmental benefit. Mitigating N 2 O emissions from agriculture may, therefore, require broader approaches, such as the internationalization of costs of GHG abatement Venterea et al, 2012), in addition to the technical solutions found by researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, more work is needed to optimize the application options of inorganic N fertilizer (such as N source, placement and application time) that allow for N-rate reductions to better match crop growth demand and mitigate N 2 O emissions without yield loss in high-yield croplands [41]. Improving these options could lessen the need for financial compensation [42].…”
Section: Mitigation Potential Of Inorganic N Fertilizermentioning
confidence: 99%